Synthesis and characterization of two different azarubrenes - Xie, Gaozhan; Hahn, Sebastian; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemical communications, 2018)
The synthesis, properties and solid state X-ray single crystal structures of two new rubrene-derivatives, viz diazarubrene (4,4′-(6,12-diphenyltetracene-5,11-diyl)dipyridine) and tetraazarubrene (5,6,11,12-tetra(pyridin-4-yl)tetracene), are reported. Both the azarubrenes are more oxidatively stable than rubrene itself and show very similar optical properties but differ in their crystal packing from that of rubrene.